Production of an inducible sucrase activity by Serpulina hyodysenteriae. - Jensen, N S (1994)
Strains of Serpulina hyodysenteriae and Serpulina innocens produced a cell-associated sucrase activity when grown in a medium containing sucrose. S. hyodysenteriae B204 sucrase activity cleaved sucrose and, to a lesser extent, raffinose and had a pH optimum of 5.7 to 6.2. This is the first report of an inducible enzyme produced by either S. hyodysenteriae or S. innocens.